Localization of a gene for myoclonus-dystonia to chromosome 7q21-q31 - Nygaard, Torbjoern G.; Raymond, Deborah; Chen, Caiping; Nishino, Ichizo; Greene, Paul E.; Jennings, Danna; Heiman, Gary A.; Klein, Christine; Saunders-Pullman, Rachel J.; Kramer, Patricia; Ozelius, Laurie J.; Bressman, Susan B. (Annals of neurology, 1999)
Essential myoclonus‐dystonia is a neurological condition characterized by myoclonic and dystonic muscle contractions and the absence of other neurological signs or laboratory abnormalities; it is often responsive to alcohol. The disorder may be familial with apparent autosomal dominant inheritance. We report a large kindred with essential familial myoclonus‐dystonia and map a locus for the disorder to a 28‐cM region of chromosome 7q21‐q31.